2013
DOI: 10.4028/www.scientific.net/amm.302.371
|View full text |Cite
|
Sign up to set email alerts
|

Channel Formation in Modified Friction Stir Channeling

Abstract: Modified friction stir channeling (MFSC) is a new approach for fabrication of a continuous, integral channel in monolithic Al plate, which is carried out in a single pass. This technique is derived from Friction Stir Processing (FSP). Tool profile and position of tool pin against work piece were designed differently from conventional Friction Stir Channeling (FSC) process. In MFSC, Fabricated channel with more regular shape than FSC process shows that the channel formation mechanism is different from FSC. So, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…It is shown in Figure 8 that the channel width remains approximately constant during channeling using MFSC process. Rashidi et al 14 studied the material flow around the tool pin body using weakened broken tool pin technique. They demonstrated that the channel width forms because of the detachment of deposited shear layers of material from tool pin body behind the pin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown in Figure 8 that the channel width remains approximately constant during channeling using MFSC process. Rashidi et al 14 studied the material flow around the tool pin body using weakened broken tool pin technique. They demonstrated that the channel width forms because of the detachment of deposited shear layers of material from tool pin body behind the pin.…”
Section: Discussionmentioning
confidence: 99%
“…Rashidi et al 14 investigated material flow and channel formation in MFSC technique using weakened tool pin method. They reported that MFSC channels are formed by extraction of material into the shoulder cavity at the front of tool pin using tilted pin.…”
Section: Introductionmentioning
confidence: 99%
“…Winiczenko [36] depict work on an effect of friction welding parameters on the tensile strength and micro-structural properties of dissimilar AISI 1020-ASTM A536 joints. [43,44], welding force, and temperature and strain distributions during friction stir processing. The step imperfection of material flow and channel formation in MFSC technique using the broken tool pin technique.…”
Section: Effect On Fsw Toolmentioning
confidence: 99%
“…The step imperfection of material flow and channel formation in MFSC technique using the broken tool pin technique. The extruded material [45] from front to the back of tool pin was showed by the cross-section view of the pin that surrounded into the work piece [43]. Previous researches also suggest that work piece temperature condition would give the better result in FSW process [43].…”
Section: Effect On Fsw Toolmentioning
confidence: 99%
“…Rashidi et al [4] claim that the stability of the channels can be solved using a non-threaded tool probe because this has the ability of maintaining the material flow constant during the process. Another study was published by Rashidi et al [7], investigating the material flow using the broken tool probe technique in order to understand the channel formation. In 2019, Pandya et al [8] have used X-ray micro computed tomography and optical microscopy to study the material flow during the FSC process.…”
Section: Introductionmentioning
confidence: 99%